EDITOR'S PREFACE - Lisdiyanti, Puspita (Annales Bogorienses, 2004)
The editors would like to announce that, in the years of 2002 and 2003, The Research Centre for Biotechnology The Indonesian Institute of Sciences (LIPI) did not publish Annales Bogorienses New Series due to some management problems. The last issue waspublished with Volume 8, Number 2, 2001. Under new editors, in this year of 2004, continuing the previous volume, this journal is published again starting with Volume 9, Number 1. In this ninth edition of Annales Bogorienses, we would also like to introduce anew look of this journal to our readers. We will I continue to publish this journal periodically twice a year (in June and December).Many thanks to all authors for their efforts, attentions, and time throughout the editing process that make this current edition become possible. Tolerance of our editorial judgments is much appreciated. We encourage our readers to submit original papers on topics of interest to life sciences researchers. June, 2004M. Ahkam SubrotoChief Editor